Essays on environmental value chain management : challenge of sustainable development - Linnanen, Lassi (1998)
This study focuses on the crossroads of environment, economy, and business. A particular research question is how the value creation process within industries and their actors is altered by environmental issues. The study relies on the view that the value creation of a corporation takes place in the interaction with its customers, suppliers, the organization itself and other stakeholders, including the natural environment. Another aim of the study is to indicate possible interdependencies between the internal and the external situational factors in building up more environmentally benign organizations. The research is based on four articles which have been published in management journals with blind peer-review process. The research approach of the study can be described by a mixture of three research traditions: action research, theory building from case studies, and constructivism. The results of this study indicate that the value creation process of companies is altered by environmental issues. These alterations include both hard management-related and soft leadership-related themes. On the harder account, two main topics gain evidence. First, systems thinking is required in the proper management of environmental issues. The focus of environmental value chain management should not be on product characteristics as such, but on improving the entire product system in a broader sense. Second, prices and the relative costs of production factors have the key role in the change towards sustainable development. Firms need economic incentives in order to advance their environmental strategies. The problem encountered is the consolidation of environmental benefits into business benefits, and the time span and the probability of the consolidation. The study also brings up two softer themes which originate from environmental value chain management. First, the importance of communication and rhetoric in understanding others and making others understand is rarely overvalued. The function of communications will extend to become a multi-dimensional tool in the legitimization of the company's overall activities in stakeholder milieu. Second, the shift in social responsibility will mirror the transition of economic actors towards sustainable development. The findings of the study have importance on both the corporate-internal and the corporate-external level of environmental management. The identification of these linkages over the external-internal divide contributes to the better understanding of the driving forces of sustainable organizations. The understanding of the complex enviro-economic and social linkages within and between organizations requires new management capabilities.